Sedentariness at Work: How Much Do We Really Sit? - McCrady, Shelly K.; Levine, James A. (Obesity (Silver Spring, Md.), 2009)
Sedentariness is associated with obesity. We examined whether people with sedentary jobs are equally inactive during their work days and leisure days. We enrolled 21 subjects of varying weight and body fat (11 men:10 women, 38 ± 8 years, 83 ± 17 kg, BMI 28 ± 5 kg/m2, 29 ± 11 fat kg, 35 ± 9% fat). All subjects continued their usual work and leisure‐time activities whilst we measured daily activity and body postures for 10 days. The data supported our hypothesis that people sit more at work compared to leisure (597 ± 122 min/day cf 484 ± 83 min/day; P < 0.0001). The mean difference was 110 ± 99 min/day. Similarly, work days were associated with less standing (341 ± 97 min/day; P = 0.002) than leisure days (417 ± 101 min/day). Although the walking bouts did not differ significantly between work and leisure (46 ± 9 vs. 42 ± 9 walking bouts/day); the mean free‐living velocity of a walk at work was 1.08 ± 0.28 mph and on leisure days was 0.94 ± 0.24 mph (P = 0.03) and the average time spent walking was 322 ± 91 min on work days and 380 ± 108 min on leisure days (P = 0.03). Estimates of the daily energetic cost of walking approximated 527 ± 220 kcal/day for work days and 586 ± 326 kcal/day for leisure days (r = 0.72, P < 0.001). Work days are associated with more sitting and less walking/standing time than leisure days. We suggest a need to develop approaches to free people from their chairs and render them more active.